Influence of Manager Personality on Strategy Implementation in Private Universities in Kenya (Journal of Organizational Psychology, 2018)
The human element reflected in psychological characteristics has been ignored by organizations despite studies pointing to the human factor as an obstacle towards successfully implementing organizational strategies. The purpose of this paper is to investigate the influence of manager personality on strategy implementation in private universities in Kenya. Data was collected from 360 top, middle level managers and lecturers in 23 private universities in Kenya. Hypothesis were tested using structural equation modelling (SEM), path analysis. The study revealed that manager personality has a positive and significant influence on the strategy implementation of private universities in Kenya.
Keywords: Strategy Implementation; Human Resource; Structural Equation Modelling